Introducción al ecomunitarismo y a la educación ambiental Lectura chilena de la obra de Sirio López Velasco - de la Fuente, José; Salas, Ricardo (Ariadna Ediciones, 2021)
The plural ecommunitarian tendency, an indispensable guide for a new historical sense, shares A. Lincoln's definition of democracy: "government of the people, by the people and for the people", where intercultural experiences constitute the fertile ground to exchange Good Living, regulated by an Environmental Education as a process of awareness made up of the "critical unveiling of the oppressions and devastations that we live-witness and the transforming-overcoming action of them." Indeed, one of the purposes is to transform society in an ecommunitarian sense at all levels, from the local to the planetarium, preparing the qualitative change that will open the doors of large-scale transition to replace capitalism with a dignified, decent coexistence, value, aesthetic, ethical, practical, scientific and participated. This education excludes machismo and homophobia, and includes respect for health and sexual education from puberty to adulthood.